Currency Regulation in the Republic of Kazakhstan in the Context of Integration - SAULEMBEKOVA, Anelya K.; ILYAS, Akylbek A.; SMAGULOVA, Raikhan U.; BAKHYT, Eric B. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The purpose of this study is to analyze currency regulation in the Republic of Kazakhstan in the context of its integration into the Eurasian Economic Union. The article analyzes dynamic changes in foreign exchange rates over the last 6 years. The authors considered exchange arrangements and devaluation stages of the national currency – tenge. The study displayed dynamics of operations in the domestic foreign exchange market. The authors suggested a number of ways to deal with inconsistencies of currency regulation and control, as well as with the monetary policy of member states of the Eurasian Economic Union. Tenge devaluation rate to the main world currencies became one of the key sensitivity indicators of the Kazakh economy to the global financial fluctuations. New realities require competent economic policy of the Republic of Kazakhstan based on both the international experience and specific development of Kazakhstan and the entire Central Asia.
Keywords: tenge devaluation, optimum currency area, exchange rate, currency integration, Eurasian Economic Union